“There’s gold in them thar stink!” : durian capitalism in the age of post-human conservation - Choo, Tze Shien (2020)
Durian is a delicacy treasured in the communities of Southeast Asia. Its distinct taste and smell turns many away, but for its fans, it is a seasonal treat that fetches a pretty hefty sum for certain varieties. China particular had fallen in love with the stinky fruit and have been creating many weird culinary concoctions with durian. Malaysia sees this as a potential industry that could have massive growth, particularly for its prized Musang King durian variety that is gaining in popularity among Chinese consumers, and with recent issues with its other crop commodity, palm oil, ranging from accusations of deforestation, loss of flora and fauna and loss of Orang Asli Indigenous rights to their ancestral land that is leading to calls for its boycott in Europe, to a fall in crude palm oil prices that is leaving this commodity in its decline, durian could potentially be Malaysia’s next big export crop. However there are concerns that it may also follow the same destructive path as palm oil, and that may be true with recent incidences of deforestation and conflicts with indigenous Orang Asli where new durian plantations are being opened in the states of Kelantan and Pahang.